On Value Distribution of Difference Polynomials of Meromorphic Functions - Zong-Xuan Chen (Abstract and Applied Analysis)
We study the value distribution of the difference counterpart Δf(z)−af(z)n of f′(z)−af(z)n and obtain an almost direct difference analogue of results of Hayman.